Identifying “best bets” for searching in chemical engineering: Comparing database content and performance for information retrieval - Badia, Giovanna (Journal of documentation, 2018)
PurposePerforming efficient literature searches and subscribing to the most comprehensive databases for interdisciplinary fields can be challenging since the literature is typically indexed in numerous databases to different extents. Comparing databases will help information professionals make appropriate choices when teaching, literature searching, creating online subject guides, and deciding which databases to renew when faced with fiscal challenges. The purpose of this paper is to compare databases for searching the chemical engineering literature.Design/methodology/approachThis paper compares journal indexing and search recall across seven databases that cover the chemical engineering literature in order to determine which database and database pair provide the most comprehensive coverage in this area. It also summarizes published, database comparison methods to aid information professionals in undertaking their own comparative assessments.FindingsSciFinder, Scopus, and Web of Science, listed alphabetically, were the leading databases for searching the chemical engineering literature. SciFinder-Scopus and SciFinder-Web of Science were the top two database pairs. No single database or pair provided 100 percent complete coverage of the literature examined. Searching a second database increased the recall of results by an average of 17.6 percent.Practical implicationsThe findings are useful since they identify "best bets" for performing an efficient search of the chemical engineering literature. Information professionals can also use the methods discussed to compare databases for any discipline or search topic.Originality/valueThis paper builds on the previous literature by using a dual approach to compare the coverage of the chemical engineering literature across multiple databases. To the author's knowledge, comparing databases in the field of chemical engineering has not been reported in the literature thus far.